Understanding the relationships between the perceptions of burnout and instability in Software Engineering - Ribeiro, Danilo Monteiro (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2022)
Changes are common during the development process of software. These changes can increase the perception of instability of software developers. Understand the relationship between human factors and Software Engineering’s process is important to try to mitigate and prevent problems. One of these factors is burnout. Burnout is considered a disease that can impact several factors in Software Engineering, such as productivity, turnover, but mainly the health of the developers. Therefore, understanding the relationship between instability and burnout can help those involved to prevent and strategize so that developers can feel better and, consequently, produce more. The main objective of this work is to identify and describe the relationship between instability and burnout in the perception of members who participate in the software development process. To reach this objective, we conducted a cross-section survey with 411 respondents, which had its sampling by convenience and self-selection. In addition to identifying relationships between variables, confirmatory factor analysis techniques were also applied. The main results of this work are: The relationship between the perception of burnout and team, technological and task instability, which is positive and significant for the dimensions of exhaustion and cynicism. For the dimension of efficacy, it was negative and weak with technological and team instabilities and does not exist with task instability. In addition, exhaustion is perceived more frequently by respondents. The instability with the highest perception of frequency by the practitioners is that of the task. The results found are important because both the market and the academy can guide their efforts to reduce the perception of burnout and instability in software engineers. Furthermore, new research can be carried out to verify the impact of instability on developers, bringing a new perspective to monitor the perception of instability in the context of software development.